Iridoids from the aerial parts of Verbena littoralis (Verbenaceae) - Castro-Gamboa, Ian (2004)
The iridoids, 6S-hydroxy-8S-methyl-4-methylene-hexahydro-cyclopenta[c]pyran-3-one and 6S,9S-dihydroxy-8S-methyl-4- methylene-hexahydro-cyclopenta[c]pyran-3-one, were isolated from the aerial parts of Verbena littoralis. Their structures and ster eochemistry were elucidated by means of NMR spectral data analysis. Both compounds showed moderate in vitro activity against gram positive and negative bacteria as well as moderate in vivo intestinal peristaltic action in mouse. The iridoids also showed mod erate free radical scavenging activity against l,l-diphenyl-2-picrylhydrazyl (DPPH) as well as antioxidant activity, the latter being evidenced by redox properties measured using E1CD-HPLC. 2004 Elsevier Ltd. All rights reserved.